Revised status, additional records, and a second species of the genus Chenzhilinus Yin & Zhou, 2024, stat. nov. (Coleoptera: Staphylinidae: Scydmaeninae) - Yin, Zi-Wei; Zhou, De-Yao (Zootaxa, 2026)
Based on the examination of newly acquired material, the subgenus Chenzhilinus Yin & Zhou, 2024 is elevated to generic rank (stat. nov.), resulting in Chenzhilinus huapingensis (Yin & Zhou, 2024), comb. nov. The diagnosis of the type species is emended and supplemented to include a characterization of the female spermatheca, alongside new distributional records. Additionally, the diversity of the genus is expanded with the description of a second species, C. yintiaolingensis Yin & Zhou, sp. nov., from Yintiaoling National Nature Reserve, Chongqing, China.